2004
DOI: 10.2169/internalmedicine.43.204
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Becker's Muscular Dystrophy Presenting with Severe Heart Failure

Abstract: We describe a rare case of Becker's muscular dystrophy (BMD) in a 28-year-old man complicated by rapidly progressing heart failure without apparent clinical signs of neuromuscular disease. He showed rhabdomyolysis, which repeatedly occurred causing acute renal failure as heart failure worsened. His serum creatine kinase (CK) level was generally below 300 IU/l. However, it exceeded more than 10,000 IU/l at the time of myoglobinuria. This suggests that the worsening of heart failure could induce rhabdomyolysis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Drosophila melanogaster taz mutants exhibited a BTHS-related phenotype, with the triad of abnormal cardiolipin, pathologic mitochondria, and motor weakness; this phenotype was suppressed by inactivation of the gene encoding type VIA calcium-independent phospholipase A 2 ( 260 ). We demonstrated that expression of MLCL AT-1 in human BTHS lymphoblasts resulted in increased MLCL AT protein, [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]linoleate incorporation into CL, CL mass, and mitochondrial function, measured in terms of succinate dehydrogenase (mitochondrial complex II) activity compared with mocktransfected BTHS lymphoblasts ( 253 ). HPLC-MS has confi rmed the validity of MLCL and CL analysis as a diag- Gaucher disease.…”
Section: Lipid Storage Disordersmentioning
confidence: 88%
See 2 more Smart Citations
“…Drosophila melanogaster taz mutants exhibited a BTHS-related phenotype, with the triad of abnormal cardiolipin, pathologic mitochondria, and motor weakness; this phenotype was suppressed by inactivation of the gene encoding type VIA calcium-independent phospholipase A 2 ( 260 ). We demonstrated that expression of MLCL AT-1 in human BTHS lymphoblasts resulted in increased MLCL AT protein, [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]linoleate incorporation into CL, CL mass, and mitochondrial function, measured in terms of succinate dehydrogenase (mitochondrial complex II) activity compared with mocktransfected BTHS lymphoblasts ( 253 ). HPLC-MS has confi rmed the validity of MLCL and CL analysis as a diag- Gaucher disease.…”
Section: Lipid Storage Disordersmentioning
confidence: 88%
“…Defects in the genes coding for calpain-3, choline kinase ␤ , AMP-dependent protein kinase, and desmin have been shown to cause LGMD2A, rostrocaudal MD, myotonic MD, and desminopathies, respectively ( Table 1 , Table 2 ) ( 4,(8)(9)(10)(11)(12). The mutations that underlie these skeletal muscle abnormalities also commonly affect cardiac muscle, resulting in a deterioration of heart function ( 1,2,(12)(13)(14)(15).…”
Section: Fatty Acid Uptake and Intracellular Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…CI may precede affection of the skeletal muscles even by years (43,77,78). Rapidly progressive heart failure without apparent clinical signs of neuromuscular disease has been reported in a 38-year-old patient with rhabdomyolysis, which was complicated by renal failure (78), and in a 33-year-old patient in whom dCMP evolved into severe heart failure, necessitating heart transplantation six years before affecting the skeletal muscle (43).…”
Section: Course and Outcome Of CI In Bmdmentioning
confidence: 99%
“…Rapidly progressive heart failure without apparent clinical signs of neuromuscular disease has been reported in a 38-year-old patient with rhabdomyolysis, which was complicated by renal failure (78), and in a 33-year-old patient in whom dCMP evolved into severe heart failure, necessitating heart transplantation six years before affecting the skeletal muscle (43). Particularly in such cases, the correct diagnosis is frequently delayed until skeletal muscle is also involved.…”
Section: Course and Outcome Of CI In Bmdmentioning
confidence: 99%